Perancangan Interior Café Go Kart di Surabaya - Henson Adisumarto (Intra, 2017)
In this busy world, entertainment can’t be separated from our lifestyle. Right now there are many kinds of entertainment facilities. One of these entertainment is go karting. It is a mini version of a car which has a simple design and usually used for racing sports. Go karts race on a small scale of circuit track. Go karts usually used for training purpose before they go into bigger machine. Go karts are usually popular among the youngsters, but there are a lot of adults who’s into karting as well. In this modern era, besides restaurant and fast food, one of the most growing food commercial is café. Café usually focused on the interior design and sells food from snack to heavy meals as well. One of the main purpose of café is to make their customers feels comfort while enjoying their meal. Café nowadays is not only used as a place to eat, but as a place to meet with other people, a place to work their assignment, etc.